English derby in philosophy: John Locke versus Derek Parfit - A. V. Nekhaev (Омский научный вестник: Серия "Общество. История. Современность")
The article presents a critical analysis of views on the problem of personal identity which are proposed by two great English philosophers — John Locke and Derek Parfit. Lockean personality is considered as a basic metaphysical structure, subject to moral responsibility for all actions performed on its behalf. Parfitian personality, in contrast, denies any identical essence through time as an extremely improbable metaphysical structure, instead assuming an existential chain of one life’s stages with psychological continuity. As an alternative to these views, a several of additional arguments are considered to support the physicist view of human nature